Deep Learning-Aided Acoustic Source Localization in Thin-Walled Waveguides - Giacomo Donati; Federica Zonzini; Stefano Mariani; Denis Bogomolov; Luca De Marchi (Research and Review Journal of Nondestructive Testing)
The timely detection of fault locations represents a critical task in Structural Health Monitoring (SHM) of thinwalled elements. In particular, the localization of acoustic emission sources is particularly important for the